KEPEMIMPINAN WANITA DALAM PERSPEKTIF HADIS - Tangngareng, Tasmin (KARSA Journal of Social and Islamic Culture, 2015)
Discourse of women's leadership is never-ending to discuss. Some Islamic theo-logical considerations has always been a major reason to support equality bet-ween men and women. This article presents the textual and contextual analysis of the leadership of women in the public sphere. It is based on textual under-standing of the Sunnah of the Prophet and the opinion of the majority of Muslim scholars poorly stated that the leadership of women in public affairs is prohi-bited, but is based on a contextual understanding is not the case with the proviso able to carry out the mandate. Islamic history records ‘Â`isyah, al-Syifâ, and Queen Balqis including a handful of women leaders who occupy public office. Therefore, in the understanding of women's leadership issues, contextual under-standing must first be considered. Copyright (c) 2015 by KARSA. All right reserved DOI: 10.19105/karsa.v23i1.615